Root exudation of mature beech forests across a nutrient availability gradient: the role of root morphology and fungal activity. Issue 2 (28th January 2020) - Meier, Ina C.; Tückmantel, Timo; Heitkötter, Julian; Müller, Karolin; Preusser, Sebastian; Wrobel, Thomas J.; Kandeler, Ellen; Marschner, Bernd; Leuschner, Christoph
Summary: Root exudation is a key plant function with a large influence on soil organic matter dynamics and plant–soil feedbacks in forest ecosystems. Yet despite its importance, the main ecological drivers of root exudation in mature forest trees remain to be identified. During two growing seasons, we analyzed the dependence of in situ collected root exudates on root morphology, soil chemistry and nutrient availability in six mature European beech ( Fagus sylvatica L.) forests on a broad range of bedrock types. Root morphology was a major driver of root exudation across the nutrient availability gradient. A doubling of specific root length exponentially increased exudation rates of mature trees by c. 5‐fold. Root exudation was also closely negatively related to soil pH and nitrogen (N) availability. At acidic and N‐poor sites, where fungal biomass was reduced, exudation rates were c. 3‐fold higher than at N‐ and base‐richer sites and correlated negatively with the activity of enzymes degrading less bioavailable carbon (C) and N in the bulk soil. We conclude that root exudation increases on highly acidic, N‐poor soils, in which fungal activity is reduced and a greater portion of the assimilated plant C is shifted to the external ecosystem C cycle.